2010
DOI: 10.1021/jf103388m
|View full text |Cite
|
Sign up to set email alerts
|

Cell Viability Effects and Antioxidant and Antimicrobial Activities of Tunisian Date Syrup (Rub El Tamer) Polyphenolic Extracts

Abstract: The aqueous-acetone polyphenolic extract of the traditionally derived date syrup, known as "Rub El Tamer", was analyzed using RP-HPLC-DAD and ESI-MS. The phenolic content of the extract was 394.53 ± 1.13 mg per 100 g of syrup with caffeoylsinapylquinic acid as the most abundant compound (72.23%). The extract exhibited strong antioxidant activities as evaluated using the ABTS (2,2'-azinobis(3-ethylbenzothiazoline-6-sulfonic acid)), DPPH (2,2-diphenyl-1-picrylhydrazyl) and FRAP (ferric reducing antioxidant power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
13
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 29 publications
5
13
1
Order By: Relevance
“…Recently some studies that supported these results were reported [28,33,34]. Thus, our study was undertaken considering the leaves of three varieties.…”
Section: Resultssupporting
confidence: 61%
“…Recently some studies that supported these results were reported [28,33,34]. Thus, our study was undertaken considering the leaves of three varieties.…”
Section: Resultssupporting
confidence: 61%
“…The spectrophotometer has been calibrated using methanol as a reference. The Trolox equivalent antioxidant capacity (TEAC) was calculated from the equation determined from linear regression, after plotting known solutions of Trolox [13].…”
Section: Evaluation Of Antioxidant Activity Using Dpph Assaymentioning
confidence: 99%
“…Thus, it is important to have a clear idea of the major phenolic families of which fruit and vegetables are comprised and the levels contained therein [10]. Several studies have been made for the determination of the antioxidant activity (AA) and total phenolic content (TPC) of date from different geographical places and varieties [11][12][13][14]. The date palm fruit possesses antioxidant and antimutagenic properties in vitro [15], therefore the AA and TPC of wide variety from Iranian date have been analyzed.…”
mentioning
confidence: 99%
“…This finding was in agreement with a previous report of Dhaouadi et al (2013). In previous reports, the use of aqueous-acetone (3/7, v/v) solvent was shown to provide a good extraction of the main polyphenols from different foods, including fruits, leaves, juices and syrups (Fattouch et al 2007;Dhaouadi et al 2011). This simple procedure lead to high yields of phenolics (Menelaos et al 2004) and removed interfering compounds, particularly cold acetone (−20°C) precipitates proteins and peptides, which absorb at 280 nm and interfere with polyphenols in HPLC analysis.…”
Section: Determination Of the Total Phenolic Contentmentioning
confidence: 99%
“…Methanol/water gradient was used according to the following solvent program: starting from 95 % A (0.5 % formic acid in Milli-Q water)and 5 % B(methanol), reaching 75 % A at 10 min, 65 % A at 30 min, 55 % A at 35 min, 55 % A at 40 min, 50 % A at 45 min, 45 % A at 50 min, 30 % A at 53 min, 25 % A at 56 min, and 20 % A at 60 min, followed by a post-time isocratic plateau for 10 min at 95 % A before the next injection. Extracts were analyzed using a modified version of the method described by Dhaouadi et al (2011). Mass spectrometry operating conditions were optimized in order to achieve maximum sensitivity values.…”
Section: Reversed Phase Hplc-dad-msmentioning
confidence: 99%